HEAVY METAL CONCENTRATIONS Cr, Cu, AND Zn OF SEAWEED Eucheuma cottonii IN MORO COSTAL WATERS KARIMUN DISTRICT RIAU ARCHIPELAGO PROVINCE - Saputri, Dian; Amin, Bintal; Ikhwan, Yusni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAK This research conducted on Juli 2018 to analyzed and compared the contain of Cr, Cu and Zn on E. cottonii from 3 station with different activity for each station. This research also to analyzed the consumption feasibility and the status of metal pollution using MPI (Metal Pollution Index). The result showed the average of concentrate of Cr 2,147 µg/g, Cu 0,9811 µg/g and Zn 9,3061 µg/g. The index value of metal pollution was 2,69 showed that the condition of water pollution at Moro, district of Karimun, Riau Island Province still at low condition. E. cottonii seaweed from this Moro's water thought that still safe for consumption as long as no more than 3,03 kg/week for Cr, 1020,83 kg/week for Cu, and 210,30 kg/week for Zn. Key words : Metal Pollution, Seaweed, E. cottonii, Riau Archipelago Province